Dispersion of Iron Oxide Nanoparticles on Oxide Nanotube for Nanocatalyst System - Anwar, Dede Miftahul (2014)

(untitled)
TiO2 nanotube arrays (TNTs) and ZrO2 nanotube arrays (ZNTs) were successfully fabricated by anodization in ethylene glycol (EG) containing 0.5 wt % NH4F at 60 V for 30 min. For the formation of nanotubes; oxidation and dissolution have been identified as two most important processes. The dissolution process occurs at the surface of the oxide, inside the pores and in between pores. Comparing TNT and ZNT; it appears ZNTs are longer with smaller diameter and thinner wall compared to TNT. Even though the anodic layer on Zr has higher value of polarization resistance (~3.92 kΩ) than TNTs (~7.82 kΩ) the dissolution rate of ZrO2 is lower (0.11 mm/year) compared to TNTs (0.416 mm/year), making TNTs are shorter. The dissolution rate of oxide on Ti and Zr is also different resulting in different dimensions. Photocurrent and charge distribution measurement exhibited excellent ability of photogenerated free charge-carriers flow in TNTs but low for ZNTs. Therefore TNTs was need as a cathode to electrodeposit iron oxide. The formation of TNTs was further studied by the use of different oxidants (H2O, H2O2 and KOH) added to the fluorinated-EG. KOH was revealed as the best oxidant to form nanotube arrays with a rate of ~ 254 nm min-1 and was suitable to be used as a template for the electrodeposition of iron oxide. For the electrodeposition lectrolyte consisting of 0.02 M FeCl3·6H2O + DI water was used. Parameters studied for this process included voltage, concentration of electrolyte and the effect of additives in the electrolyte. The growth mechanism of the nanoparticles and their morphology were described. From electron microscopy images, it is clearly observed that the presence of fine nanoparticles on the TNTs substrates were obtained xxi in electrolyte added with glycerol. Higher distribution of particles was observed with increasing potential applied to the cathode foil. Size and shape of the particles was also a function of the voltage. The average diameter of the spherical particles prepared at −1 V was ± 41.7 nm. Increasing the voltage to -3V resulted in particles exhibit rice-like morphology with the average diameter and length are ± 44 nm and 130 nm, respectively. X-ray diffraction (XRD) and Raman spectroscopy measurements showed that the nanoparticles consisted of magnetite (Fe3O4), maghemite (γ-Fe2O3) and hematite (α-Fe2O3) after annealing at 450oC for 2h (air). Photodegradation measurement confirmed the photocatalytic properties of hybrid photocatalyst system fabricated. ~90% degradation of metal orange (MO) was observed on the TNTs|iron oxide system which is higher than that in pristine TNTs (~75%). Photocurrent and Mott-Schottky measurement exhibited that the sample has the highest photocurrent generated (~35 mA cm-2) under solar simulator.